Impaired facial and vocal emotion decoding in schizophrenia is underpinned by basic perceptivo-motor deficits*. Issue 6 (2nd November 2017) - Mangelinckx, C.; Belge, J. B.; Maurage, P.; Constant, E.
ABSTRACT: Introduction : Emotional decoding impairments have been largely demonstrated in schizophrenia for facial and prosodic stimuli, when presented separately. Nevertheless, the exploration of crossmodal integration has been far less considered, despite its omnipresence in daily social interactions. Moreover, the role played by basic visuo-motor impairments in unimodal and crossmodal decoding remains unexplored. Methods : Thirty-two patients were compared with 32 matched controls in an emotional decoding task including unimodal (visual and auditory) and crossmodal (congruent and incongruent) conditions. A control perceptive task was also conducted to take potential low-level perceptual deficits into account. Results : Schizoprenic patients presented lower performance and higher reaction times for both unimodal tasks (visual and auditory) and crossmodal conditions. Moreover, reaction times for the visuo-perceptive task were also significantly longer for patients compared to controls. Conclusions : The consistency of the results across unimodal and crossmodal tasks suggests a globalised emotional impairment in schizophrenia, independent of the sensorial modality and crossmodal nature of the stimuli. Centrally, given the results in the visuo-perceptive task, the impairments observed for emotional recognition appears at least partly explained by primary cognitive deficits, namely reduced processing speed.